Application of essential oils in meat packaging: A systemic review of recent literature. (February 2022) - Smaoui, Slim; Ben Hlima, Hajer; Tavares, Loleny; Ennouri, Karim; Ben Braiek, Olfa; Mellouli, Lotfi; Abdelkafi, Slim; Mousavi Khaneghah, Amin
Abstract: During preparation, processing, and distribution, the spoilage of meat products has been causing a negative economic impact in the meat industries. In addition, lipid/protein oxidation and deterioration resulting from microorganisms' development are other concerns verified during the storage of meat and meat derivatives. In this sense, the meat industry has designed biopolymers-based materials containing biomolecules as active packaging to diminish losses and improve the shelf-life of these products. Here, we examined the loading of essential oils in the active films and coatings. Their impact on the chemico–physio–mechanico properties and antioxidant and antibacterial potential of the numerous biopolymer films for packaging meat and derived products are discussed. The potential use of essential oils incorporated into biopolymer network matrices of these films was also evaluated. This review also covers the biological effects of different types of edible films and the influence of these functional packaging on improving meat product quality. Interestingly, active films containing essential oil present a future approach and an environmentally friendly solution in the meat industry. In general, active food packaging revealed suitable technology to improve meat quality and reduce waste in the food industry. Graphical abstract: Image 1